Moderating Effect of Corporate Governance on the Relationship Between Sustainability Reporting and Firm Value of Listed Oil and Gas Companies in Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The modern business environment necessitates continuous organizational adaptation to maintain competitive value in evolving markets. Firm valuation, conceptualized as the premium investors are willing to pay for corporate ownership, serves as a comprehensive indicator of both tangible assets and managerial efficacy in value creation (Massie et al., 2017; Setiadharma & Machali, 2017). Contemporary corporate reputation management extends beyond financial metrics to incorporate environmental, social, and governance (ESG) dimensions, with robust non-financial disclosure frameworks becoming increasingly critical for capital acquisition and shareholder value optimization.This paradigm shift has occasioned the development of sustainability reporting (SR) as an institutionalized practice for disclosing organizational impacts across economic, environmental, and social domains (Global Reporting Initiative, 2017a). As a relatively recent innovation, SR has emerged as a strategic tool for ESG risk assessment, opportunity identification, and organizational transparency enhancement (Global Reporting Initiative, 2017). The implementation of SR frameworks facilitates improved strategic planning, operational adaptability, and business continuity in an era where sustainability considerations significantly influence corporate decision-making and stakeholder expectations.Within the Nigerian context, SR adoption remains predominantly voluntary, with mandatory compliance limited to premium board-listed entities. Current motivations for SR implementation frequently emphasize philanthropic corporate social responsibility (CSR) initiatives and reputational enhancement, raising concerns about potential greenwashing practices (Okwuosa, 2024).